2016
DOI: 10.1097/jsm.0000000000000271
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Quadratus Femoris Muscle Rupture After Yoga Exercises

Abstract: We present a case of a female patient with left groin pain after intense yoga exercises. The patient presented abnormal pattern of gait with no swelling over the groin, thigh, or buttock. Magnetic resonance imaging demonstrated a tear of the quadratus femoris muscle with an associated extensive hematoma formation. Patient was treated with a rehabilitation program consisting of nonsteroidal anti-inflammatory drugs and physiotherapy. At the follow-up control, the patient had improved her pain and flexibility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…There are few publications regarding the incidence of traumatic injury to the obturator internus or quadratus femoris, with the majority of case reports involving the short external rotators in adult soccer or tennis players. 3,6,10,12,14,16 Symptoms can manifest as groin, gluteal, hip, or posterior thigh pain usually with difficulty during ambulation.…”
Section: Discussionmentioning
confidence: 99%
“…There are few publications regarding the incidence of traumatic injury to the obturator internus or quadratus femoris, with the majority of case reports involving the short external rotators in adult soccer or tennis players. 3,6,10,12,14,16 Symptoms can manifest as groin, gluteal, hip, or posterior thigh pain usually with difficulty during ambulation.…”
Section: Discussionmentioning
confidence: 99%
“…He also suggested that manual therapy has a positive effect on pain, range of motion, muscular strength and level of the functional activity on frozen shoulders following intervention by physiotherapists. However, manual or massage therapy can cause complications, such as muscle bleeding, muscle rupture, or myositis ossi cans [17,18]. Sasanuma et al [19] reported that MRI in patients with severe frozen shoulder after manipulation showed capsule tears, labrum tears, and bone bruises in the humeral head.…”
Section: Discussionmentioning
confidence: 99%
“…In strains or tears, edema is found at the myotendinous junction, predominantly on the femoral side (29). Isolated strains or tears of the QF muscle are extremely rare and are usually associated with nearby tendon or muscle strain injuries, typically followed by a sudden and unusual sharp pain (41).…”
Section: Diagnosis Of Ifimentioning
confidence: 99%
“…This is an area where QF muscle edema can compress the nerve and cause sciatic neuritis as a result of local irritation (Figure 2) (34). (17), surgical reattachment of the hamstring tendon (10), intermuscular lipoma (14), and even by extreme stretching of the hip (41). In recent studies, ischiofemoral narrowing has been observed without previous surgery or trauma to the hip region (32), and abnormal signals of the QF muscle without ischiofemoral narrowing have also been observed (29), which makes the pathogenesis of IFI uncertain.…”
Section: Patient Profile and Mechanism Of Injurymentioning
confidence: 99%
See 1 more Smart Citation